Knowledge spillovers and patent citations: Trends in geographic localization, 1976-2015 - Hyuk-Soo Kwon; Jihong Lee; Sokbae Lee; Ryungha Oh (Centre for Microdata Methods and Practice (cemmap), 2019)
This paper examines the trends in geographic localization of knowledge spillovers via patent citations, extracting multiple cohorts of new sample US patents from the period of 1976-2015. Despite accelerating globalization and widespread perception of the "death of distance," our matched-sample study reveals significant and growing localization effects of knowledge spillovers at both intra- and international levels after the 1980s. Increased localization effects have been accompanied by greater heterogeneity across states and industries. The results are robust to various methods of proxying the existing geography of knowledge production.
Keywords: O33; O34; O51; C81; 330; Innovation; knowledge spillovers; patent citation; agglomeration